Acceleration at z>1? - Amendola, Luca (Arxiv, 2002)
Most models of dark energy predict the beginning of the accelerated epoch at z <= 1. However, there are no observational or theoretical evidences in favor of such a recent start of the cosmic acceleration. In fact, a model of dark energy coupled to dark matter is explicitely constructed that a) is accelerated even at high z; b) allows structure formation during acceleration; and c) is consistent with the type Ia supernovae Hubble diagram, including the farthest known supernova SN1997ff at z~1.7 . It is shown that the accelerated epoch in this model could have started as early as z~5.